2016
DOI: 10.1108/heswbl-05-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

The Chartered Manager Degree Apprenticeship: trials and tribulations

Abstract: Purpose In 2014, the UK Government introduced a new form of apprenticeship, the Degree Apprenticeship, which extends across all undergraduate degree and master’s degree levels, maps to professional standards, and which is now embedded within governmental levies of large businesses. The purpose of this paper is to share early experiences of developing these Degree Apprenticeships, and consider the processes deployed to achieve it. Design/methodology/approach This paper combines desk research with reflections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…Apprenticeship training in the United Kingdom is delivered at three different levels -'foundation', 'advanced' and 'higher'. Introduced in 2015, 'degree apprenticeships' are higher apprenticeships which allow participants to earn a bachelor's or master's degree while being employed fulltime and securing at least an apprentice's minimum wage (Bishop and Hordern, 2017;Rowe et al, 2016). Importantly, the government funds apprenticeship training in England.…”
Section: Comparison Of Hard and Soft Skillsmentioning
confidence: 99%
“…Apprenticeship training in the United Kingdom is delivered at three different levels -'foundation', 'advanced' and 'higher'. Introduced in 2015, 'degree apprenticeships' are higher apprenticeships which allow participants to earn a bachelor's or master's degree while being employed fulltime and securing at least an apprentice's minimum wage (Bishop and Hordern, 2017;Rowe et al, 2016). Importantly, the government funds apprenticeship training in England.…”
Section: Comparison Of Hard and Soft Skillsmentioning
confidence: 99%
“…Such factors have resulted in Universities restricting entry to apprenticeship programmes with some offering entries once a year whilst others have moved to entries at the start of each semester. Whilst flexibility of approach was previously highlighted by Carter (2010), Bravenboer (2016) and Rowe, Perrin, and Wall (2016) as a key factor for success, respondents from the University sector suggested that flexibility and being responsive to employer needs are two of the main challenges and opportunities facing Universities wishing to deliver D&HLAs.…”
Section: University Challenges and Opportunitiesmentioning
confidence: 99%
“…If D&HLAs require apprentices to be registered on an undergraduate or postgraduate programme this may limit, or exclude, many independent training providers from delivering these qualifications; unless the qualifications they deliver are integrated and accredited as part of a degree award. Rowe, Perrin, and Wall (2016) concluded that a critical success factor for D&HLAs is that University infrastructures acknowledge and respond to the nuances of work-based programmes. They recommend that in general University structures need to become more flexible in terms of collaborative provision and the way in which resources are allocated, arranged and assessed when delivering D&HLAs.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, one study reviews the development of a Chartered Manager Degree Apprenticeship from the perspective of the programme designers, citing misinformation about the value of the degree, grappling with standards bodies and internal institutional resistance as challenges faced [16]. Rowe et al later break down several challenges in the areas of skills development, mentoring and employer-driven pedagogic approach, and collected qualitative data about these challenges from managerial positions in companies [15].…”
Section: Introductionmentioning
confidence: 99%